Exogenous intrapleural injection of interleukin-27 may improves outcome and prognosis in patients with tuberculous pleural effusion. (October 2019) - Gan, Yiling; Guo, Shuliang; Zhu, Youming; Jiang, Jie; Tan, Yuanrong
Abstract: We hypothesize that exogenous intrapleural injection of interleukin-27 may improve outcome and prognosis in patients with tuberculous pleural effusion (TPE). Studies have found that the balance of Th1/Th2 determines the development trend of TPE. High concentrations of IFN-γ and TNF-α in pleural effusion are associated with pleural adhesion in patients with TPE. Interleukin-27 is a member of the IL-12 family, and IL-27 has a dual regulatory effect on Th1 immunity. On one hand, IL-27 can promote the initial CD4+ T cell proliferation by inducing the expression of T-bet, IL-12Rβ2 and ICAM-1 in the initial CD4+ T cells, and also promote its differentiation into Th1 cells and IFN-γ production in the early infection. On the other hand, in the case of high Th1 polarization, IL-27 induced STAT3 phosphorylation and inhibited TNF and IL-12 production in activated peritoneal macrophages, indicating a novel feedback mechanism by which IL-27 can modulate excessive inflammation, thereby preventing damage to the body caused by excessive immune response. Studies haves confirmed that after stimulation of antigen by mononuclear cells in TPE, the Th1 and Th2 cell subsets and Th1/Th2 ratio markedly increase, and the increase of Th1 is more obvious than that of Th2. Therefore, compared to patients with TPE in the high-level IL-27 group, we hypothesized that pleural effusion is absorbed more slowly, pleural thickening is more obvious, pleural adhesions are more extensive, and the incidence of thoracic collapse is higher in the low-level IL-27 group under the same conditions of anti-tuberculosis treatment. However, exogenous intrapleural injection of IL-27 may induce Stat3 phosphorylation and inhibit TNF and IL-12 production, finally reduces the secretion of IFN-γ and TNF-α. This negative regulation inhibits the excessive inflammatory reaction caused by tuberculosis infection, reduces pleural adhesion, pleural thickening and local pleural tissue damage, thereby improving the prognosis of patients.